Volar Translunate Perilunate Dislocation: Case Report and Analysis of Review of Literature - Bhat, Anil K.; Kurup, Jayakrishnan K. Narayana; Acharya, Ashwath M. (Journal of Hand and Microsurgery, 2019)
Volar translunate perilunate dislocations are the rarest form of perilunate dislocations with only a handful of cases reported till now. The injury mechanism is not uniform, and the pattern of injury does not follow traditional classifications. We report a case of volar translunate perilunate dislocation with a review of literature of very few previous reported cases of these rare injuries.
Keywords: volar; translunate; perilunate dislocation; greater arc; lesser arc